The effect of spice and herbs mixture on electrolytes and liver and renal function in patients with type 2 diabetes mellitus - Khattak, Muhammad Muzaffar Ali Khan; Mohd Shukri, Nor Azwani; Mahmood, Tahir; Ahmed, Qamar Uddin; Rahimlou, Mehran (Shiraz University of Medical Sciences, 2025)
Background: Diabetes has a prevalent nature and still presents a signicant public health challenge. This study investigated the eect of spice and herbs on serum biochemical parameters in type 2 diabetes mellitus (T2DM). Methods: The spice and herbs procured from local market were processed by cleaning, washing, crushing, freeze-drying, formulating, and encapsulating in doses of 2, 4, and 6 grams. Thirty patients with T2DM were assigned to 3 equal groups to receive each mentioned dose fed for 30 days. On day 1 and 31, fasting blood samples were collected and analyzed for electrolytes (Na, K and Cl), urea, creatinine, liver enzymes (AST: aspartate aminotransferase, ALT: Alanine aminotransferase, ALP: alkaline phosphatase), fasting blood glucose (FBG), and lipid prole. The data were further statistically analyzed. Results: The electrolytes, urea, creatinine, and liver enzymes remained within the normal ranges after the consumption of spices and herbs. There was a reducing trend for HbA1c level after intake of spices and herbs. Total cholesterol and low-density lipoprotein cholesterol (LDL-C) decreased by -10.08-7.36% and high-density lipoprotein cholesterol (HDL-C) increased in 2 and 6 gram consuming groups; whereas it decreased in the 3 gram consuming group. The concentration of triglycerides (TG) decreased notably with increasing doses of spices and herbs. Conclusion: Consumption of spices and herbs mixture was demonstrated to have benecial eects on kidney and liver function, blood glucose level and lipid prole in T2DM patients. These ndings suggest the potential therapeutic value of incorporating spices and herbs into the management of T2DM.